“We Should Not Be Like a Dinosaur”—Using AI Technologies to Provide Formative Feedback to Students - Tony Burner; Yngve Lindvig; Jarl Inge Wærness (Education Sciences)
Artificial intelligence (AI) technologies have the potential to enhance learning, teaching, and assessment by providing AI-generated feedback to students. This study used five different AI plug-ins and four different knowledge bases for the optimization of feedback in classroom formative assessments. The sample consisted of 26 students and 13 teachers at five secondary schools in Norway. Interviews and unstructured observations were used to collect data. The findings indicate that AI-generated feedback is appreciated by both students and teachers. It provides immediate subject-specific, concrete, and relevant feedback. High-performing students were motivated to further improve their writing. However, some students found the feedback to be too general or complicated, and the teachers who had not conducted whole-term periodic planning struggled with using AI for formative assessment purposes. Finally, both students and teachers contend that the teacher needs to have the last word when AI takes over formative feedback procedures.